2018
DOI: 10.17816/ov11141-46
|View full text |Cite
|
Sign up to set email alerts
|

Zonular instability in patients with pseudoexfoliative syndrome: the analysis of 1000 consecutive phacoemulsifications

Abstract: Phacoemulsification (PHACO) is the gold standard of cataract surgery. Сataract surgery in eyes with pseudoexfoliative (PEX) syndrome is associated with increased risk of intra- and postoperative complications. Zonular laxity is one of the main causes of surgical complications. Purpose. To assess the degree of zonular weakness in patients with PEX. Materials and methods. 1010 eyes (580 eyes with PEX and 430 eyes without it) that underwent consecutive PHACO at the Ophthalmology Department No 5 of the City Multif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Consequently, the use of a CTR was necessary in these eyes. Other studies have also reported a higher percentage of zonulopathy in the group of patients with PEX [ 19 ]. In four (1.44%) cases among our patients with PEX syndrome, the rupture of the posterior capsule and related complications prevented the primary implantation of an IOL.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Consequently, the use of a CTR was necessary in these eyes. Other studies have also reported a higher percentage of zonulopathy in the group of patients with PEX [ 19 ]. In four (1.44%) cases among our patients with PEX syndrome, the rupture of the posterior capsule and related complications prevented the primary implantation of an IOL.…”
Section: Discussionmentioning
confidence: 87%
“…All these factors contribute to an increased rate of intraoperative complications, including zonular dehiscence (separation or weakening of the lens zonular fibers), posterior lens capsule rupture, vitreous loss, and nucleus drop [ 2 , 6 , 13 , 18 , 19 , 20 ]. Additionally, a higher rate of postoperative complications has been reported, including corneal edema and descemetitis, elevated intraocular pressure (IOP) spikes, inflammation, anterior capsule phimosis, posterior capsule opacification, and intraocular lens (IOL) dislocation, often within the capsular bag [ 6 , 13 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some ocular and systemic conditions may result in zonular weakness: pseudoexfoliation syndrome (PEX), with or without glaucoma, Marfan's syndrome, retinitis pigmentosa and blunt trauma are the most common causes. 11 PEX and blunt trauma can lead to anterior chamber depth (ACD) fluctuations 12,13 which results in effective lens position (ELP) change. In cases of Marfan's syndrome, zonular fibers may be elongated and disintegrated leading to lens decentration.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 , 9 PEX is known to be a risk factor for various intra- and postoperative complications during PhE, including rupture of the zonules of Zinn and posterior capsule, vitreous body prolapse, anterior capsular contraction syndrome, IOL decentration and dislocation. 9 , 10 One of the main causes of intraoperative complications in PEX is zonular weakness. Frequency of its occurrence in PEX ranges from 8.4% to 10.6%.…”
mentioning
confidence: 99%